Republic Act No. 9208 - ---, --- (Review of Women's Studies, 2004)
An Act to Institute Policies to Eliminate Trafficking in Persons Especially Women and Children, Establishing the Necessary Institutional Mechanisms for the Protection and Support of Trafficked Persons, Providing Penalties for Its Violations, and for Other Purposes